Порівняльний аналіз кіберстратегій України та США - Шпількін, А. Р. (ХНУРЕ, 2023)
This work is dedicated to the study of the existing national cybersecurity strategies, its best practices and comparing the relevant documents of United States of America and Ukraine. The rapid development of information and communications technology entails a certain list of challenges for all people. And some of them can be addressed by proper regulations and norms that provide guidance on a state or interstate basis.